The deubiquitinase USP36 promotes snoRNP group SUMOylation and is essential for ribosome biogenesis. (14th April 2021) - Ryu, Hyunju; Sun, Xiao‐Xin; Chen, Yingxiao; Li, Yanping; Wang, Xiaoyan; Dai, Roselyn S; Zhu, Hong‐Ming; Klimek, John; David, Larry; Fedorov, Lev M; Azuma, Yoshiaki; Sears, Rosalie C; et al.
Abstract: SUMOylation plays a crucial role in regulating diverse cellular processes including ribosome biogenesis. Proteomic analyses and experimental evidence showed that a number of nucleolar proteins involved in ribosome biogenesis are modified by SUMO. However, how these proteins are SUMOylated in cells is less understood. Here, we report that USP36, a nucleolar deubiquitinating enzyme (DUB), promotes nucleolar SUMOylation. Overexpression of USP36 enhances nucleolar SUMOylation, whereas its knockdown or genetic deletion reduces the levels of SUMOylation. USP36 interacts with SUMO2 and Ubc9 and directly mediates SUMOylation in cells and in vitro . We show that USP36 promotes the SUMOylation of the small nucleolar ribonucleoprotein (snoRNP) components Nop58 and Nhp2 in cells and in vitro and their binding to snoRNAs. It also promotes the SUMOylation of snoRNP components Nop56 and DKC1. Functionally, we show that knockdown of USP36 markedly impairs rRNA processing and translation. Thus, USP36 promotes snoRNP group SUMOylation and is critical for ribosome biogenesis and protein translation. SYNOPSIS: The deubiquitinase USP36 also promotes protein SUMOylation and is essential for ribosome biogenesis and protein translation. USP36 promotes nucleolar protein SUMOylation. USP36 is the first identified DUB/SUMO promoting dual function protein. USP36 promotes snoRNA protein group SUMOylation. USP36 is critical for rRNA processing, translation and cell growth. Abstract : The deubiquitinase USP36 also promotes protein SUMOylation and is essential for ribosome biogenesis and protein translation.